Landfill Site Suitability Assessment Based on GIS and Multicriteria Analysis: A Case Study of Kirkuk City - Hana Kareem Shekho; Muntadher Aidi Shareef (Al-Kitab Journal for Pure Sciences)
This study looks at the environmental and socioeconomic aspects of possible landfill locations in Kirkuk City, Iraq, as well as their spatiotemporal appropriateness. This study used different types of data, including Landsat satellite imagery, soil texture, groundwater level, and slope. The Analytic Hierarchy Process (AHP) was utilized for multi-criteria decision analysis of possible landfill sites, linear regression was employed for population projection, and a Convolutional Neural Network (CNN) was utilized for Normalized Difference Vegetation Index (NDVI)/ Normalized Difference Built-up Index (NDBI) prediction. The suitability ratings for prospective dump sites were produced using the AHP-based Geographic Information Index (GIS) techniques. The results reveal that the selection of landfill locations minimizes environmental effects and advances environmentally sound waste management. The technique provides a framework for assessing the appropriateness of dump sites in various geographical areas. Moreover, the projections for the future emphasize Kirkuk City's need for upgraded waste management facilities. Furthermore, urban planners and politicians in Kirkuk City may benefit greatly from this research's data-driven approach to landfill site selection, which takes social and environmental concerns into account and has implications for sustainable waste management techniques.